2011
DOI: 10.1038/sc.2011.28
|View full text |Cite
|
Sign up to set email alerts
|

The administration of high-dose methylprednisolone for 24 h reduced muscle size and increased atrophy-related gene expression in spinal cord-injured rats

Abstract: Objective: Administration after spinal cord injury (SCI) of methylprednisolone (MP) for 24-48 h has been suggested to improve functional outcome. The safety of this approach has been questioned because of the known adverse effects of glucocorticoids on skeletal muscle and the immune system. The purpose of this study was to explicitly test adverse effects of regimen of MP administration on skeletal muscle. Study design: Male rats underwent spinal cord transection at T9-T10, followed by an intravenous injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Consistent with a previous report, 6 MP significantly reduced body weight (Po0.001) and the wet weights of triceps, plantaris, soleus and gastrocnemius, compared with weights for SCI-Vehicle animals (Po0.01, Figure 2). Triceps was chosen for these studies as a major weight-bearing muscle of the forelimb, and gastrocnemius was selected, because like triceps, it is an extensor and has a mixed fiber type.…”
Section: Body and Muscle Weightssupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with a previous report, 6 MP significantly reduced body weight (Po0.001) and the wet weights of triceps, plantaris, soleus and gastrocnemius, compared with weights for SCI-Vehicle animals (Po0.01, Figure 2). Triceps was chosen for these studies as a major weight-bearing muscle of the forelimb, and gastrocnemius was selected, because like triceps, it is an extensor and has a mixed fiber type.…”
Section: Body and Muscle Weightssupporting
confidence: 80%
“…Support for these concerns comes from findings that in SCI rats, this regimen of MP induced a more than 50% decrease in triceps muscle weights at 7 days after injury, even though this muscle remained neurologically intact. 6 In a case series, five of six patients, who were administered MP, had histological and electromyelographic evidence of myopathy, whereas none of those not administered this agent demonstrated these abnormalities. 4 Such findings suggest that administration of very high doses of MP damages skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that both Sham and SCI groups underwent this procedure which we believe would provide a control for any potential confounding effects of this surgery on miR expression. While effects of these surgeries on muscle were not examined in the current study, we have previously reported that expression of several muscle atrophy genes is increased at early time points after either laminectomy [31], and that these alterations resolve by 14 days. While we cannot exclude an influence of these surgeries on skeletal muscle in the Sham and SCI rats used in the current study, our prior results suggest that any effects are small relative to those resulting from the SCI itself.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of the muscle atrophy induced by steroids is relatively rapid. In the case of the rat it can occur within 24h (32). Moreover, it is possible that sepsis-induced FOX01 is also mediated by glucocorticoids (33).…”
Section: Is There a Common Mechanism By Which Glucocorticoids Affect mentioning
confidence: 99%